1991
DOI: 10.1093/clinchem/37.6.838
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum estradiol and progesterone concentrations to the excretion profiles of their major urinary metabolites as measured by enzyme immunoassay and radioimmunoassay

Abstract: Paired daily blood and urine samples were collected from 10 apparently healthy premenopausal women to compare the hormone profiles of estradiol (E2) and progesterone in serum with those of estrone conjugates (E1Conj) and pregnanediol-3-glucuronide (PdG) in urine. Serum hormones were measured by radioimmunoassay (RIA) kits, whereas the urinary steroid metabolites were assessed by both RIA and enzyme immunoassay (EIA). RIA and EIA values for urinary E1Conj and PdG were not different, and both methods produced ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
1
5

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(156 citation statements)
references
References 15 publications
5
145
1
5
Order By: Relevance
“…A 1.5-to 2.0-fold E 1 C increase above the mean early follicular baseline has been observed 2 to 3 days before the E 1 C peak, which occurs in the majority of M. fascicularis between Days 8 and 15 of the menstrual cycle (Behboodi et al, 1991). These results are similar to those reported for women (Munro et al, 1991). A single 2-hour mating before or the day of the E 1 C peak resulted in a conception rate of 38.6%, which is comparable to a 40% conception rate in contemporary controls mated every other day over a 5-day period during midcycle (three times).…”
Section: Detection Of Ovarian Cycle Phasesupporting
confidence: 87%
See 1 more Smart Citation
“…A 1.5-to 2.0-fold E 1 C increase above the mean early follicular baseline has been observed 2 to 3 days before the E 1 C peak, which occurs in the majority of M. fascicularis between Days 8 and 15 of the menstrual cycle (Behboodi et al, 1991). These results are similar to those reported for women (Munro et al, 1991). A single 2-hour mating before or the day of the E 1 C peak resulted in a conception rate of 38.6%, which is comparable to a 40% conception rate in contemporary controls mated every other day over a 5-day period during midcycle (three times).…”
Section: Detection Of Ovarian Cycle Phasesupporting
confidence: 87%
“…ELISA, which may now be used for accurate measurement of CG in serum or urine in macaques (Munro et al, 1991), is a particularly valuable method for studies in which changes in CG concentrations may be relevant. In 2001, Shimizu et al (2001) reported on a noninstrumented ELISA for pregnancy detection in macaques that used a color change visible to the naked eye, similar to a human pregnancy test.…”
Section: Detection and Monitoring Of Pregnancymentioning
confidence: 99%
“…Testosterone concentration was measured using enzyme immunoassay methods previously validated for mouse urine (Munro et al 1991;Muir et al 2001). Testosterone was obtained from Sigma chemicals, UK, and antibodies to testosterone and corresponding horseradish peroxidise conjugates from the Department of Population Health and Reproduction at the University of California, USA.…”
Section: S C E N T -M a R K I N G T R I A L Smentioning
confidence: 99%
“…Estrone glucuronide is an inactive metabolite of estradiol and its urinary concentrations have been found to closely parallel serum concentrations. 17 Estrone glucuronide was measured by enzyme immunoassay using an estrone-conjugated horseradish peroxidase system as previously described. Urinary creatinine was measured by colorimetric methods.…”
Section: April 2003mentioning
confidence: 99%